ANALISIS FLYPAPER EFFECT, PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN KHUSUS PADA BELANJA MODAL - Paramartha, Made Fajar; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine whether there is the phenomenon of flypaper, Local Revenue (PAD), and Special Allocation Fund (DAK) in Regency / City in the province of Bali. The study population was all regencies / cities in Bali, sampling technique sampling of this study is saturated because the entire population in this study the research sample. The analytical tool used in this research is multiple linear analysis with SPSS version 19.0 indicates (a) Revenue (PAD) affects capital expenditures, (b) Funds Aloksi (DAU) has no effect on capital expenditures, (c) Funds Special Allocation (DAK) significant effect on capital expenditures, (d) Revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) jointly affect the Capital Expenditure
Keywords: PAD, General Allocation Fund, Special Allocation Fund, flypaper and Capital Expenditure.